Fermentation of bamboo shoots using mature coconut water and its stability during storage at different conditions - Changkiew, Yaowalak; Tanganurat, Palida; Sansenya , Sompong; Changpasert, Waleewan; Chotiko, Arranee (Journal of Applied Research on Science and Technology (JARST), 2024)
Fermented-bamboo-shoots are a common raw ingredient used in several Thai local dishes. However, contamination of harmful and undesirable microorganisms in the fermented bamboo shoots has been reported due to improper and long fermentation processes. Mature coconut water (MCW) could shorten the bamboo shoot fermentation process and improve the product quality. This study aimed to develop fermented bamboo shoots using mature coconut water and determine their stability during storage in different conditions. Bamboo shoots from Prachinburi province were mixed with 25 g/kg of Kosher salt and fermented with MCW to obtain fermented bamboo shoots with coconut water (FBSC) at room temperature. Traditional fermented bamboo shoots (TFBS), prepared using 100 g/kg of Kosher salt, were used as a control. After fermentation, the samples were packed in polypropylene (PP) or polyethylene terephthalate (PET) bags and stored at different temperatures for 60 days. The number of bacteria, pH, and total acidity (TA) were determined during fermentation and storage, as well as the color changes of the shoots. The results indicated that in the fermentation process, MCM with low salt concentration could effectively increase the number of lactic acid bacteria (LAB) greater than the traditional method. The number of LAB in FBSC was 9.78±0.43 CFU/mL of LAB, while TFBS had 8.08±0.02 log CFU/mL. Lower pH was significantly found in FBSC (3.89±0.01) than in TFBS (4.00±0.01), while TA of FBSC was significantly higher than that of TFBS, which were 11.25±0.01 g/L and 6.00±0.01 g/L, respectively. During storage, it was found that fermentation methods, types of packaging, and storage temperatures significantly affect the shoot colors but not pH and TA. PET bags could better delay the browning reaction of the fermented shoots than PP bags. The higher storage temperatures were, the faster color changes were observed. This study indicated that MCW could be used as fermentation media for bamboo shoots.